Estudo de qualidade de vida e depressão dos receptores de transplante renal, relacionado com doadores com critérios expandido de doação - Monteiro, Patricia Amaral [UNIFESP] (2016)
Introduction: The quality of life has been the focus of interest of researchers since it can be very revealing about the clinical situation that patients under replacement therapy, as kidney transplantation, are passing through. To measure the quality of life and depression in kidney transplant patients with expanded criteria donors, we use the WHOQOL-Abbreviated instrument, since it evaluates the patient in their physical, psychological, social relationships and environmental context, and the CES-D, which assesses the degree of depression. These instruments were applied to assess if there is some degree of depression and assess what level of quality of life in renal transplant patients associated with expanded criteria donors. Method: This study is cross-cohort work in which the perception of quality of life and depression of patients were evaluated in a single interview through questionnaires. Data were presented as mean ± standard deviation with minimum and maximum value of each variable and presented in tables. Control group was not used because the data were only descriptive, not having the object of comparison. Results: 36 patients receiving a kidney graft from donor with expanded criteria were included. Depression presents a slight increase trend among the female group. The quality of life showed improvement with personal patient satisfaction with their own health and showed a perception of negative aspects such as pain, discomfort, negative feelings, and dependence on medication. Conclusion: Although, it was detected depression and alteration in quality of life, it was possible to identify in what extent factors related to expanded criteria donors might have interfered with the results, demonstrating the need for more studies on this group of donor not only in Brazil, but in a more global context.